2017
DOI: 10.1007/s00122-017-2857-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of modern tomato breeding germplasm for deciphering the genetic control of agronomical traits by Genome Wide Association study

Abstract: A panel of 300 tomato accessions including breeding materials was built and characterized with >11,000 SNP. A population structure in six subgroups was identified. Strong heterogeneity in linkage disequilibrium and recombination landscape among groups and chromosomes was shown. GWAS identified several associations for fruit weight, earliness and plant growth. Genome-wide association studies (GWAS) have become a method of choice in quantitative trait dissection. First limited to highly polymorphic and outcrossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 102 publications
2
39
2
3
Order By: Relevance
“…Third, we used a relatively high stringency for association analysis in this study. The p -values of 1.19–1.30 × 10 −4 used here were much lower than 0.005 used in other studies (Xu et al, 2013; Zhang et al, 2016; Bauchet et al, 2017), which could decrease the power of association analysis. Fourth, it has been reported that the genome of cherry tomato accessions is a mosaic composed of polymorphisms of S. pimpinellifolium and S. lycopersicum (Blanca et al, 2015), which might also cause the failure of association mapping.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Third, we used a relatively high stringency for association analysis in this study. The p -values of 1.19–1.30 × 10 −4 used here were much lower than 0.005 used in other studies (Xu et al, 2013; Zhang et al, 2016; Bauchet et al, 2017), which could decrease the power of association analysis. Fourth, it has been reported that the genome of cherry tomato accessions is a mosaic composed of polymorphisms of S. pimpinellifolium and S. lycopersicum (Blanca et al, 2015), which might also cause the failure of association mapping.…”
Section: Discussioncontrasting
confidence: 55%
“…cerasiforme , and 865.7 kb in S. lycopersicum accessions (Lin et al, 2014). A recent study analyzing 300 tomato accessions with 11000 SNPs suggests that the LD decay ranges from 0.2 cM (73 kb) to 49 cM (47 Mb) at chromosomal level (Bauchet et al, 2017). In this study, the LD decay range from 3.0 to 47.2 Mb on 12 chromosomes with an overall of 28.5 Mb in the whole genome, which is larger than previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations